Amino-modified chitosan/gold tailings composite for selective and highly efficient removal of lead and cadmium from wastewater. (December 2022) - Zhang, Yi; Haris, Muhammad; Zhang, Lei; Zhang, Chao; Wei, Ting; Li, Xiang; Niu, Yuhua; Li, Yongtao; Guo, Junkang; Li, Xiaojing
Abstract: In this work, a novel amino-modified chitosan/tailings composite (CS-PEI-nGT) was successfully synthesized from gold tailings particle treated by ball milling (nGT), chitosan (CS) and polyethyleneimine (PEI) as raw materials, for Lead (Pb(Ⅱ)) and Cadmium (Cd(Ⅱ)) removal from aqueous solutions. The CS-PEI-nGT was characterized by using FTIR, XRD, SEM, BET, TGA and XPS techniques. The results showed that CS-PEI-nGT had maximum adsorption capacity of 192.78 mg·g −1 and 99.46 mg·g −1 for Pb(Ⅱ) and Cd(Ⅱ) respectively at pH 5. The adsorption kinetics was described well by pseudo-second-order kinetic adsorption model, and suggested that chemisorption as the rate-controlling step for adsorption of Pb(Ⅱ) and Cd(Ⅱ). The isotherm data was accurately explained by Langmuir model with higher correlation coefficient (R 2 ) of 0.9911 and 0.9642 for Pb(Ⅱ) and Cd(Ⅱ) respectively. In addition, CS-PEI-nGT retained its selective adsorption capacity for Pb(Ⅱ) and Cd(Ⅱ), compared to other metals such as Zn(Ⅱ), Mn(Ⅱ), Mg(Ⅱ) and Al(Ⅲ). The mechanism of the adsorption was investigated and the results revealed that amino (-NH2 ), silicon oxide groups (Si–O) and hydroxyl (-OH) functional groups on composite surface were accountable for metals adsorption, suggesting surface complexation, electrostatic interactions and ion exchange. Our work presents a promising strategy for tailings recycling and highly efficient removal of toxic metals ions from wastewater. Graphical abstract: Image 1 Highlights: Gold tailings nanoparticle was obtained by wet ball milling and applied to the removal of heavy metals. A novel amino-modified chitosan/tailings composite was synthesized from the gold tailings particle as raw materials, for Pb(Ⅱ) and Cd(Ⅱ) removal from aqueous solutions. The composite retained its excellent removal capacity and selective for Pb(Ⅱ) and Cd(Ⅱ). The mechanism is attributed to the joint contribution of surface complexation, electrostatic interactions and ion exchange.